Collaborative science narrows knowledge gaps in marine biological invasions to advance a national framework - Romeu S. Ribeiro; Cristina Espírito Santo; Susana Celestino; Marta Mamede; João J. Castro; Teresa Cruz; Teresa Silva; David Jacinto; Cátia Bartilotti; Jorge Lobo-Arteaga; Miriam Tuaty-Guerra; João Canning-Clode; et al. (Marine Pollution Bulletin, 2026)

Insights into meat marination technology: an overview of current advances - Bruno Fonsêca Feitosa; Álvaro Gustavo Ferreira da Silva; Gilmar Freire da Costa; Ana Rita Ribeiro de Araújo Cordeiro; Juliana Lopes de Lima; Leidiana Elias Xavier; Ítallo Vicente de Mesquita; Maria Eduarda Pessoa de Araújo; Narciza Maria de Oliveira Arcanjo (International Journal of Gastronomy and Food Science, 2026)

Retraction notice to “Collapse of scallop Nodipecten nodosus production in the tropical Southeast Brazil as a possible consequence of global warming and water pollution” [Sci. Total Environ. 904 (2023) 166873] - Cristiane Thompson; Leonardo Bacha; Pedro Henrique C. Paz; Marcelo de Assis Passos Oliveira; Braulio Cherene Vaz Oliveira; Claudia Omachi; Caroline Chueke; Marcela de Lima Hilário; Michele Lima; Luciana Leomil; Thais Felix-Cordeiro; Thalya Lou Cordeiro da Cruz; et al. (Science of The Total Environment, 2026)

Assessing global and regional remote sensing products for burned area mapping: A comparative study in the Brazilian cerrado - Vera Laísa da Silva Arruda; Ane Alencar; Ana Carolina Moreira Pessôa; Filipe Viegas de Arruda; Bárbara Costa da Silva; Dhemerson Estevão Conciani; Júlia Z. Shimbo; Fernanda Figueiredo Ribeiro; Wallace Silva; Osmar Abílio de Carvalho Júnior (Remote Sensing Applications: Society and Environment, 2026)

Nuclear receptor disruption contributes to 2,4-dichlorophenol-induced developmental toxicity: Evidence from network toxicology and zebrafish analysis - Rafael Xavier Martins; Romério de Oliveira Lima Filho; Cleyton de Sousa Gomes; Matheus Carvalho; Maria Eduarda de Souza Maia; Bianca Mataribu; Catarina Serrão; Marcos Vinicius Porto Medeiros; Milena Pereira Arruda; Ana Julia Antunes de Magalhães; Juliana Alves da Costa Ribeiro Souza; Thaís Feitosa Guimarães; et al. (Environmental Research, 2026)

Imine-metal complexes showing remarkable antiparasitic activity against Trypanosoma cruzi: different modes of action modulated by the ligand and the metal ion - Marcelo C. Portes; Luan dos Santos Vianna; Maria Luiza G. Gallego Rosa; Silvana Ribeiro; Wagner A. de Souza Júdice; Anderson Lima dos Santos; Marcos Brown Gonçalves; Filipe D.Dalmatti A. Lima; Helena M. Petrilli; Maria J. Manso Alves; Ana M. da Costa Ferreira (Chemico-Biological Interactions, 2026)

First description of the complete mitochondrial genomes of the species Amblyomma humerale and Amblyomma geayi (Acari: Ixodidae), Amazon, Pará, Brazil - Lucas Henrique da Silva e Silva; Fábio Silva da Silva; Sandro Patroca da Silva; Paulo Henrique Gomes de Castro; Anita Roberta Stone; Leonardo Henrique Almeida Hernández; Daniel Damous Dias; Sâmia Luzia Sena da Silva; Lucia Aline Moura Reis; Hanna Carolina Farias Reis; Liliane Leal das Chagas; Tania Cristina Alves da Silveira da Cunha; et al. (Experimental and Applied Acarology, 2026)
The genus Amblyomma koch, 1844 contains approximately 138 species, which are mainly distributed in the Afrotropical, Oriental, Neotropical and Australasian zoogeographic regions. This is an important group of arthropod vectors responsible for transmitting a wide range of etiological agents that cause infections and diseases in humans and animals, and is therefore of great interest to public and veterinary health.This study describes and characterizes, for the first time, the complete mitochondrial genomes of the species Amblyomma humerale and Amblyomma geayi . The obtained sequences presented a circular molecule structured in 37 functional subunits with 13 Protein-Coding Genes (PCGs), 22 transfer RNAs (tRNAs), two ribosomal RNA (rRNAs), two replication control regions, and two regions called “Tick-box”. The phylogeny reconstructed using the maximum likelihood method, based on the 13 concatenated PCGs, produced a monophyletic group for the genus Amblyomma , including the investigated sequences. A. humerale and A. geayi were grouped into the clades formed by the subgenera Walkeriana and Anastosiella , respectively. By integrating complete sequences, the approach adopted expands the number of comparable characters, reduces biases associated with the use of isolated mitochondrial markers, and contributes to better statistical support for the recovered nodes, resulting in more stable and interpretable phylogenetic topologies. The data and information generated in this study can contribute to future taxonomic and evolutionary research on the genus Amblyomma .

Bioactive additive for modulation of immune responses and gut microbiota in weanling pigs: In vitro and in vivo study - Ana Julia Carrasco Buzatto; Isabela Cristina Colaço Bez; Mariana Regina Rosa Catoia; Bianca Faria Cuman; Gustavo Zigovski de Paula; Jessica Müller Urnau; Thiago Pereira Ribeiro; Saulo Henrique Weber; Gregório Murilo de Oliveira Júnior; Vivian Vezzoni de Almeida; Paulo Levi de Oliveira Carvalho; Leandro Batista Costa (Research in Veterinary Science, 2026)

Epidemiological dynamics and spatial expansion of animals sporotrichosis in the Brazilian Amazon - Eduardo Rodrigues de Souza; Helena Cristina Cardoso Coelho; Ana Carolina Coelho Caporazzi; Cely Gomes Ferreira; Francisco da Costa Leão; José Francalino Vital; Leíse Gomes Fernandes; Wagner Cosme Morhy Terraza; Sônia Maria da Silva Carvalho; Junior Ribeiro Carvalho (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Evaluation of the genes CYP85A2, BZR1, and CAD1 in the attenuation of cadmium in seedlings of the species Schizolobium parahyba var. amazonicum (Huber ex Ducke) Barneby (PARICÁ) under different concentrations of 24-epibrassinolide - Erick dos Santos Ribeiro; Cândido Ferreira de Oliveira Neto; Ednaldo da Silva Filho; Igor Guerreiro Hamoy; Ana Ecídia de Araújo Brito; Dênmora Gomes de Araújo; Juliana Freitas do Nascimento; Evelyn Luane Pinheiro de Figueiredo; Dayane dos Santos Costa; Lilian Tatiana Costa Barros; Vinícius Oliveira Amancio (Environmental Science and Pollution Research, 2026)
The Amazonian species paricá ( Schizolobium parahyba var. amazonicum ( Huber ex Ducke ) Barneby ) accumulates cadmium (Cd) primarily in the roots, but the lack of understanding of gene modulation in response to this metal and the phytohormonal mechanisms complicates its relevance in the rehabilitation of degraded areas. Therefore, the present study aims to examine the expression of the CYP 85 A 2 and BZR1 genes, precursors of 24-EBL, in the production of chelating proteins by the CAD1 gene in seedlings of the Paricá species, under various concentrations of CdCl 2 and 24-EBL. The experiment was conducted in a growth room at the Laboratory of Studies on Biodiversity of Higher Plants (EBPS) at the Federal Rural University of Amazon (UFRA), Belém-Pará Campus, following a completely randomized experimental design (CRD), in a 4 × 3 factorial scheme, totaling 60 experimental units with four treatments of CdCl 2 (0, 50, 100, and 150 µM) and three doses of 24-epibrassinolide (0, 20, and 40 nM). The data were subjected to analysis of variance (ANOVA) ( p < 0.05), and the differences between treatments were analyzed using Tukey’s test ( p < 0.05). The biometric variables indicated a significant reduction in root length due to the harmful effect of CdCl 2 . Additionally, losses in Chl a , Chl b , and Chl a + b were observed due to the entry of Cd 2+ into the leaf tissues. Despite this, the CYP 85 A 2 , BZR1 , and CAD1 genes showed greater expression in the aerial part with varying doses of 24-EBL, while CAR and ACN were affected by increased CdCl 2 , indicating a genetic adjustment in the upper parts of the plants to cope with Cd toxicity and maintain biological functions.

Fertility decline induced by subchronic exposure to an atrazine–mesotrione mixture in male Wistar rats - Luiz Otávio Guimarães-Ervilha; Izabela da Silva Lopes; Mírian Quintão Assis; Isabela Pereira da Silva Bento; Thainá Iasbik-Lima; João Victor Leles Faria; Luís Miguel Ribeiro de Almeida; Renner Philipe Rodrigues Carvalho; John Lennon de Paiva Coimbra; Renê Chagas da Silva; Fernanda Aparecida Ferrari Soares; Ana Paula Mitiko Fialho Toma; et al. (Toxicology, 2026)

Erector spinae plane block with bupivacaine contributes to intraoperative opioid sparing but provides limited postoperative pain control in cats undergoing elective ovariohysterectomy under continuous propofol infusion - Ana Paula Longo Ribeiro; Gilberto Serighelli-Júnior; Felipe Comassetto; Lorenzo Schmitz Borsato Cavagnari; Camila Fernanda Baehr Cavagnari; Atila Souza Rocha Freire de Santana; Maryana de Souza Matos; Ayla da Costa Wittaczik; Nilson Oleskovicz (Veterinary Research Communications, 2026)
This study evaluated the intraoperative and postoperative analgesic effects of an ultrasound-guided erector spinae plane (ESP) block with bupivacaine in cats undergoing elective ovariohysterectomy. Sixteen healthy client-owned female cats (with, 2.62 ± 0.46 kg; and, 23.06 ± 20.34 months) were randomly assigned to two groups ( n = 8 each). All animals received dexmedetomidine (2.5 µg/kg, intramuscularly), followed by propofol administered to effect for induction and maintained as a continuous rate infusion beginning at 0.3 mg/kg/min adjusted as necessary. Ultrasound-guided bilateral ESP blocks were performed at the first lumbar vertebra using 0.25% bupivacaine (0.5 mL/kg per side) in the bupivacaine group, (GB) or 0.9% saline in the saline group (GS). Intraoperative Cardiopulmonary variables and nociceptive responses were recorded, and fentanyl (2.5 µg/kg, IV) was administered as analgesia rescue. Postoperative pain was assessed over 24 h using the UNESP–Botucatu Multidimensional Pain Scale (short-form) and the Feline Grimace Scale, with buprenorphine rescue (20 µg/kg, IM). Cats in GB required fewer intraoperative fentanyl rescue (27 vs. 35 administrations), corresponding to a 22.85% reduction in total fentanyl rescue compared with the GS, however, no statistical difference between groups ( p = 0.5976). Intraoperative heart rate and systolic arterial pressure increased during periods of greater surgical stimulation in both groups, with no significant between-group differences. No significant differences were observed in postoperative requirement of analgesic rescue. ( p = 0.9554). These findings indicate that the ESP block with bupivacaine provides effective intraoperative opioid-sparing analgesia but limited postoperative benefit, supporting its use as part of a multimodal analgesic approach in feline abdominal surgery.

Concrete Jungle: habitat heterogeneity acts as environmental filter on multidimensional diversity of fruit-feeding butterflies in urban Savannahs of Cerrado biome - Geraldo de Brito Freire; Israel Pereira dos Santos Ribeiro; Ana Carolina Lacerda de Matos; Sofia Coradini Schirmer; Eduardo Guimarães Santos; Fernanda Vieira da Costa; Felipe M. Gawryszewski; Lee A. Dyer; Onildo J. Marini-Filho; Pedro Togni (Urban Ecosystems, 2026)

The haunting challenge of the trends and pathway assessments on newly introduced non-indigenous species in European seas - Okko Outinen; Peter A.U. Stæhr; Romeu S. Ribeiro; Aina Carbonell; Robert Comas-González; Lydia Png-Gonzalez; Maite Vázquez-Luis; Ann-Britt Florin; Rahmat Naddafi; Arjan Gittenberger; Hans Jakobsen; Ana C. Costa; et al. (Marine Pollution Bulletin, 2026)

Ruminally unprotected guanidinoacetic acid supply in sheep diets is effective in improving oocyte quality through mitochondrial function and by modulating regulatory gene markers that encode follicular growth, estrogen synthesis, and antiapoptotic activity - Jhennyfe Nobre de Sena; Camila Muniz Cavalcanti; Alfredo José Herrera Conde; Bruna Vitória de Freitas Alves; Larissa Fernandes Baia Cesar; Marta da Costa Sousa; Yohana Huicho Miguel; Louhanna Pinheiro Rodrigues Teixeira; Fernando Felipe da Silva Pereira; Gildas Mbemya Tetaping; Juliana Paula Martins Alves; César Carneiro Linhares Fernandes; et al. (Animal Reproduction Science, 2026)

Alternative strategic control of Rhipicephalus microplus in the Cerrado of Minas Gerais, Brazil, by exploiting abiotic conditions - Vinicius da Silva Rodrigues; Maria Clara Oliveira Sousa; Rodrigo da Costa Maia; Giovanna Cirqueira Ribeiro Borges; Amanda Ferreira Rezende; Ana Carolina Sousa; Gustavo Martins Felix Silva; Adriane Suzin; Matheus Augusto Ferreira Fernandes; Matias Pablo Juan Szabó (Veterinary Parasitology, 2026)

Life cycle assessment of insect farming: a review - Nuno Ribeiro; Ana Cláudia Dias; Rui Costa; Olga M. C. C. Ameixa (The International Journal of Life Cycle Assessment, 2026)
Purpose Insect rearing for food and feed has gained momentum as an emerging sector aimed at addressing global food security and enhancing sustainability. However, several environmental studies raised concerns and questioned this growing industry, especially in the European context. This review aims to systematically summarize the current available knowledge on Life Cycle Assessments (LCA) in insect production systems, evaluate how different LCA methods and production configurations influence the environmental and sustainability outcomes and determine major trends and knowledge gaps, emphasizing what is sufficiently robust and what needs a critical re-examination. Methods A systematic review of the available literature of peer-reviewed case studies that employed LCA methodology for insect mass was performed. Data were extracted on key methodological aspects: functional units (e.g., insect biomass, protein, fat, waste treated), system boundaries (e.g., cradle-to-gate, cradle-to-plate), allocation methods (economic, mass, system expansion), impact assessment methods (ReCiPe, TRACI, CML, IPCC), and data sources (primary and secondary databases such as Ecoinvent and Agri-footprint). The review also considered production scale, insect species, geographical distribution, and end-use purposes. A SWOT analysis was also performed to assess the internal strengths and weaknesses, and external opportunities and threats of LCA applications in insect farming, presenting implications for future research and policy. Results and discussions Insects have several advantages over traditional livestock; nonetheless, comparability of LCA studies is challenged by methodological disparities, most notably in the way functional units, system boundaries, allocation procedures and impact assessment methods are defined. The strength of evidence is also restricted when considering data quality of direct emissions, energy consumption, water use, and nutritional content. Consequential LCA is still scarcely used, though it can help to capture market dynamics and system-wide consequences. Feed category, energy carriers, and technological processing exert influences on environmental performance, with waste-based feeding and replacement fossil energy with renewable energy sources as recognized sustainable options. Proximity of insect farms with related industry sectors, that produce adequate feedstock, while reducing feeding stuff transportation costs, can increase sustainability. Conclusions Although insect farming is considered a potential and sustainable option for future food systems, its utmost potential can be reached only through consistent knowledge, data precision improvements and more widespread use of consequential approaches, being LCA an important tool to achieve the sustainability goals. The development of consistent tools to evaluate sustainability trade-offs, increase the regulations flexibility, and build markets, is critical to place insect farming as a viable, and resilient component of innovative food systems.

Effect of the physical state of plant material on the essential oil yield of Cyperus sesquiflorus (Torr.) Mattf. & Kük. (Cyperaceae) - Andressa Cristina Ribeiro Assunção; Carlos Luiz da Silva; Lailson César Andrade Gomes; Sâmia Andrícia Souza da Silva; Ticiano Gomes do Nascimento; Hugo Henrique do Nascimento; Péricles Barreto Alves; Emmanoel Vilaça Costa; Ana Paula do Nascimento Prata Lins (Vegetos, 2026)

Spatial Pattern of Litter Decomposition and Soil Carbon and Nitrogen Stocks in an Agrosilvopastoral System in the Cerrado Biome - Jaqueline de Cássia de Oliveira; Igor Costa de Freitas; Evander Alves Ferreira; Ana Clara Santos Duarte; Juliana Martins Ribeiro; Demerson Luiz de Almeida Barbosa; Warley Rodrigues Oliveira; Diana Signor; Miguel Marques Gontijo Neto; Elaine Cristina Teixeira; Luiz Arnaldo Fernandes; Leidivan Almeida Frazão (Journal of Soil Science and Plant Nutrition, 2026)
Purpose This study evaluated the effects of eucalyptus trees in an agrosilvopastoral (ASPS) system on litter dynamics, CO₂ efflux, soil fertility, and soil carbon (C) and nitrogen (N) stocks, in order to understand how these factors contribute to nutrient cycling and the restoration of soil quality, comparing it with nominal pasture (NP) and native vegetation (NV). Methods Five treatments were assessed, including three locations within a nine years-old ASPS established with double-row eucalyptus planting, based on proximity to the trees: P1 (area between the double rows), P2 (2.5 m), and P3 (7.0 m). Litter deposition and decomposition and CO 2 efflux were monitored monthly for one year. Soil samples collected up to 50 cm depth were analyzed for bulk density, fertility attributes, and carbon and nitrogen stocks. Results Annual litter deposition was highest at P1 (5.85 Mg ha⁻¹ yr⁻¹), decreasing with distance from trees. Decomposition rates were highest at P3 and P1, with faster turnover (half-life ~ 203–224 days), and lowest at P2 (279 days). CO₂ efflux was highest at P1 (6.798 µmol m⁻² s⁻¹), likely due to increased soil moisture near the trees. Litter input contributed to maintaining K and P levels, despite no fertilisers being applied after the first five years of ASPS establishment. Soil C and N stocks were highest in NV (115.4 and 11.3 Mg ha⁻¹, respectively), and similar between NP (92.4 and 8.7 Mg ha⁻¹) and ASPS (89.9 and 8.9 Mg ha⁻¹). The findings highlight the role of litter in nutrient cycling and maintaining soil C and N in ASPS. Conclusion Our findings highlight the significant potential of agrosilvopastoral systems to enhance soil fertility and boost carbon and nitrogen stocks in tropical environments. However, these benefits are strongly contingent upon the effective and integrated management of both tree and pasture components. Without appropriate management practices, the full benefits of such systems may not be achieved, limiting their potential to enhance soil quality over time compared to conventional pastures and native vegetation. Graphical Abstract

Behavioral and biochemical effects of benzophenone-3 ingestion in dusky damselfish Stegastes fuscus - Jéssica Ferreira de Souza; Mayara Moura Silveira; Ana Luisa Pires Moreira; Juliana Alves Costa Ribeiro Souza; Rafael Xavier Martins; Davi Farias; Francisco Carlos da Silva Junior; Ana Carolina Luchiari (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Solid-liquid phenolic compound transfer and kinetic modeling during cachaça maturation using tropical woods - Jackson de Souza Moreira; Ana Beatriz da Costa Pereira Silva; Normando Ribeiro-Filho; Flávio Luiz Honorato da Silva; Líbia de Sousa Conrado (Food and Bioproducts Processing, 2026)

Enantioselective toxicity of 3,4-methylenedioxypyrovalerone in Daphnia magna: Assessment of morphophysiological, behavioural, biochemical and reproductive responses - Ariana Pérez-Pereira; Ana R. Carvalho; Pedro A. Costa; Bruno B. Castro; João S. Carrola; Virgínia M.F. Gonçalves; Ana R.L. Ribeiro; Ana Sofia Almeida; Carla Fernandes; Maria E. Tiritan; Cláudia Ribeiro (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Neem oil emulsions stabilized by natural and synthetic emulsifiers: a study on physical stability and antifungal activity - Vitor Emanuel de Souza Gomes; Fernanda Luisa Lüdtke; Raquel Costa Chevalier; Letícia Aliberti Galego Alves da Silva; Mayara Silva Rodrigues; Liliana de Oliveira Rocha; Rosiane Lopes da Cunha; Ana Paula Badan Ribeiro; Luís Marangoni Júnior (Food Research International, 2025)

IL-17 as a putative hallmark of intense arthralgia and age-related serum immune mediator networks during acute chikungunya fever - Caio Wilker Teixeira; Jonai Pacheco Dias; Lizandra Morgado-Santos; Ismael Artur da Costa-Rocha; Sarah Giarola-Silva; Ágata Lopes-Ribeiro; Letícia Gomes-de-Pontes; Thaiza Aline Pereira Santos; Joaquim Pedro Brito-de-Sousa; Erik Vinicius de Sousa Reis; Ana Carolina Campi-Azevedo; Andréa Teixeira-Carvalho; et al. (Inflammation Research, 2025)

Potential immunoprophylactic use of a multi-epitope protein of CD4+ and CD8+ T cells against visceral leishmaniasis in Balb/c mice - Scarleth Silva Costa; Naianda Rezende Ribeiro; Luiza dos Reis Cruz; Gabriel José Lucas Moreira; Vivian Tamietti Martins; Daniela Pagliara Lage; Danniele Luciana Vale; Camilly Vitória Silva Costa; Nathalia Coral Galvani; Gabriel Paulino Luiz; Maria Eduarda de Oliveira; Ricardo Andrez Machado-de-Ávila; et al. (Research in Veterinary Science, 2025)

Performance Improvement of Downdraft Biomass Gasification Using a Physical Barrier and Low-Cost Catalysts for Syngas Enhancement - Mateus Alves Magalhães; Angélica de Cássia Oliveira Carneiro; Tiago Guimarães; Márcio Aredes Martins; Gabriel Browne de Deus Ribeiro; Aylson Costa Oliveira; Barbara Corradi; Vinicius Resende de Castro; Solange de Oliveira Araújo; Paulo Fernando Trugilho; Iara Fontes Demuner; Ana Márcia Macedo Ladeira Carvalho (BioEnergy Research, 2025)

Effect of injection conditions on the efficiency of intrafollicular immature oocyte transfer (IFIOT) - Ana Caroline Chaves Vall Nicolás; Otávio Augusto Costa de Faria; Marcelo Sant Ana Borges; Nayara Ribeiro Kussano; Ivo Pivato; Carlos Frederico Martins; José Felipe Warmling Sprícigo; Margot Alves Nunes Dode (Theriogenology, 2025)

Conventional and alternative treatment of mastitis in dairy goats - Magna Coroa Lima; Richard Costa Polveiro; David Germano Gonçalves Schwarz; Ana Julia Silva Moreira; Isis de Freitas Espeschit Braga; Mariana de Barros; José Dantas Ribeiro Filho; Maria Aparecida Scatamburlo Moreira (Small Ruminant Research, 2025)

Effects of rainfall patterns on the trophic conditions of a near-pristine Amazon estuary (Brazil) - Brenda Ribeiro Padilha da Silva; Luci Cajueiro Carneiro Pereira; Ana Vila-Concejo; Rauquírio Marinho da Costa (Regional Studies in Marine Science, 2025)

Correction: Antifungal activity of guanidine compounds - Alexandra Daniela Barrios Eguiluz; Caroline Barcelos Costa Orlandi; Rafael Días Do Espírito Santo; Eduardo Henrique Zampieri; Luana Ribeiro dos Anjos; Maria José Soares Mendes Giannini; Ana Marisa Fusco-Almeida; Sandro Roberto Valentini; Cleslei Fernando Zanelli; Tatiana Maria de Souza-Moreira; Eduardo René Pérez González (Brazilian Journal of Microbiology, 2025)

Antifungal activity of guanidine compounds - Alexandra Daniela Barrios Eguiluz; Caroline Barcelos Costa Orlandi; Rafael Días Do Espírito Santo; Eduardo Henrique Zampieri; Luana Ribeiro dos Anjos; Maria José Soares Mendes Giannini; Ana Marisa Fusco-Almeida; Sandro Roberto Valentini; Cleslei Fernando Zanelli; Tatiana Maria de Souza-Moreira; Eduardo René Pérez González (Brazilian Journal of Microbiology, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Phenotypic and behavioral variation as a mechanism behind the invasive potential of a predatory neotropical fish - Marcos Ribeiro da Costa Gaspar; Angelo Antonio Agostinho; Paula Araújo Catelani; Rodrigo Fernandes; Ana Clara Sampaio Franco; José Luis Costa Novaes; Danielle Peretti; Ana Cristina Petry; Fernando Mayer Pelicice (Hydrobiologia, 2025)

Inhibition of calcineurin as a strategy for biofilm control: Trichosporon spp. as a case study - Bruno Nascimento da Silva; Ana Raquel Colares de Andrade; Francisco Eilton Sousa Lopes; Ana Luiza Ribeiro Aguiar; Fernando Victor Monteiro Portela; Maria Laina Silva; Brendda Miranda Vasconcelos; José Júlio Costa Sidrim; Débora Souza Collares Maia Castelo-Branco; Rossana de Aguiar Cordeiro (Biofouling, 2025)

Spread of antimicrobial-resistant clones of the ESKAPEE group: From the clinical setting to hospital effluent - Damaris Krul; Bianca Ribeiro da Silva Negoseki; Adriele Celine Siqueira; Ana Paula de Oliveira Tomaz; Érika Medeiros dos Santos; Inayara de Sousa; Thais Muniz Vasconcelos; Isabelle Christine Rodrigues Marinho; Lavinia Nery Villa Stangler Arend; Dany Mesa; Danieli Conte; Libera Maria Dalla-Costa (Science of The Total Environment, 2025)

Immersive virtual contexts, engagement, and emotions: How do these factors influence sensory acceptance? - Fernanda Nascimento da Silva; Luis Antonio Minim; Tarcísio Lima Filho; Ana Alice da Silva Xavier Costa; Márcia Cristina Teixeira Ribeiro Vidigal; Valéria Paula Rodrigues Minim (Food Research International, 2025)

Comparative anatomical description of the thoracic limb muscles of Puma concolor, Leopardus wiedii and Leopardus pardalis - Jessica da Costa da Silva; José Gabriel Ribeiro Alves; Érika Branco; Ana Rita de Lima (Zoomorphology, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Unveiling Swelling and Erosion Dynamics: Early Development Screening of Mirabegron Extended Release Tablets - Ana S. Sousa; J. Serra; C. Estevens; R. Costa; António J. Ribeiro (AAPS PharmSciTech, 2024)
Although the development of extended release (ER) matrices has been extensively investigated, understanding the most appropriate mechanism of drug release to achieve the desired release remains a cost- and time-consuming challenge in the early stages of formulation development. This study aimed to investigate the early stage of developing ER hydrophilic matrix tablets containing mirabegron as a model drug, focusing on the effects of polymer type, diluent type, and polymer amount on critical quality attributes (CQAs), namely, tablet swelling and erosion behavior. A full factorial design was employed to explore the interactions of control factors through multivariate regression analysis, emphasizing the application of quality by design (QbD) principles. The swelling and erosion performances of 72 formulations were evaluated. The swelling data were fitted to the Vergnaud model. Finally, in vitro drug release profiles were investigated for four of the formulations studied. The polymer type, diluent type, and polymer amount had distinct effects on the swelling and erosion behavior of the ER matrix tablets. Compared with those with isomalt (G720) or dextrate (DXT), formulations with polyethylene glycol 8000 (P8000) consistently exhibited greater swelling. Additionally, higher molecular weight was correlated with increased swelling within the same polymer type. Hydroxypropylmethylcellulose (HPMC) and polyethylene oxide (PEO)-based formulations showed higher swelling rates, while polyvinyl alcohol (PVA-80) displayed the highest erosion percentage. The findings highlight the significance of incorporating early-stage screening designs to maximize efficiency and optimize time and resource. This approach enables the development of a comprehensive understanding of drug release mechanisms from ER matrix tablets. Graphical abstract

In Vivo Test to Evaluate the Cytotoxicity and Genotoxicity of Natural Zeolite (NZ) Functionalized with Silver Nanoparticles (NZ-AgNPs) on Erythrocytes of Yellowtail Tetra Fish Astyanax lacustris - Josiane Rodrigues Rocha da Silva; Camila Oliveira de Andrade; Anna Carla Ribeiro; Paula Derksen Macruz; Elizabeth da Costa Neves FernandesAlmeida Dua; Rosângela Bergamasco; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes (Biological Trace Element Research, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Hyperkeratotic gastritis in two-toed sloths (Choloepus didactylus) from wildlife rescue - Washington A. Pereira; David F. Conga; Antônio M. Costa; Adriana C. Jaques; Alexsandro P. Damasceno; Samara C. Loura; Pedro H. Portela; Andressa B. Menezes; Ana S. Ribeiro (Journal of Comparative Pathology, 2024)

Doxorubicin-galactomannan nanoconjugates for potential cancer treatment - Laís Ramos Monteiro de Lima; Maria Francilene Souza Silva; Gisele S. Araújo; Fábio de Oliveira Silva Ribeiro; Irisvan S. Ribeiro; Cláudia Pessoa; Raimundo N. Costa Filho; José Delano B. Marinho Filho; Ana Jersia Araújo; Durcilene Alves da Silva; Judith P. Andrade Feitosa; Regina Celia Monteiro de Paula (Carbohydrate Polymers, 2024)

Comprehensive review of the skin use of bakuchiol: physicochemical properties, sources, bioactivities, nanotechnology delivery systems, regulatory and toxicological concerns - Filipa Mascarenhas-Melo; Mariana Marques Ribeiro; Kaveh Hatami Kahkesh; Sagarika Parida; Kiran D. Pawar; K. Velsankar; Niraj Kumar Jha; Fouad Damiri; Gustavo Costa; Francisco Veiga; Ana Cláudia Paiva-Santos (Phytochemistry Reviews, 2024)
Bakuchiol is a meroterpene that has recently aroused great interest in the cosmetic and pharmaceutical industries. Its main source is the seeds of Psoralea corylifolia, a medicinal plant native to Asia, despite having a wide geographical distribution. However, this medicinal herb faces endangerment due to low seed germination rates and high seedling mortality. In this context, this review article highlights studies that have focused on describing plant regeneration from root fragments. Subsequently, given its morphological similarity to other species, a technique that can be used to verify the authenticity of the plant and prevent counterfeiting is also mentioned and explored. Additionally, a “green” extraction method for obtaining bakuchiol is presented, and the possibility of obtaining bakuchiol through chemical synthesis routes is also explored. Furthermore, we provide an exhaustive description of bakuchiol's wide range of biological activities, with particular relevance to the skin. The main skin bioactivities of bakuchiol include antifungal, antibacterial, antioxidant, anti-inflammatory, antiaging, depigmenting, and anticancer. However, the particular physicochemical properties of bakuchiol require and benefit from the development of innovative skin delivery systems that allow its encapsulation. These include micro- and nano-sized systems for therapeutic and cosmetic applications, which are also carefully described in this review article. Finally, regulatory issues, metabolic considerations, and toxicological concerns related to the use of bakuchiol in cosmetic and dermopharmaceutical formulations will be addressed, relating not only to the user but also to the environment. Graphical abstract

Heterotopic ovarian allotransplantation in a caprine model: Effects of implant site on morphological parameters - Antonio Renilson Sousa Vieira; Leda Maria Costa Pereira Bersano; Fabiana Aparecida Santilli Brandão; Celso Henrique Souza Costa Barros; Francisco Carlos de Sousa; Ana Luiza de Sousa Rodrigues; Benner Geraldo Alves; Francisco Denilson Rodrigues Gomes; Ana Paula Ribeiro Rodrigues; Dárcio Ítalo Alves Teixeira (Animal Reproduction Science, 2024)

Exploring bacterial diversity and antimicrobial resistance gene on a southern Brazilian swine farm - Mariana Costa Torres; Gabriela Merker Breyer; Manuel Adrian Riveros Escalona; Fabiana Quoos Mayer; Ana Paula Muterle Varela; Vasco Ariston de Carvalho Azevedo; Mateus Matiuzzi da Costa; Flavia Figueira Aburjaile; Marcio Dorn; Bertram Brenig; Marisa Ribeiro de Itapema Cardoso; Franciele Maboni Siqueira (Environmental Pollution, 2024)

Histological biomarkers and microbiological parameters of an estuarine fish from the Brazilian Amazon coast as potential indicators of risk to human health - Gustavo Henrique Rodrigues Vale de Macedo; Jonatas da Silva Castro; Wanda Batista de Jesus; Ana Laíssa Pereira Costa; Rafael do Carmo Silva Ribeiro; Samanda de Jesus Roland Pires; Rita de Cássia Mendonça Miranda; Wellyson da Cunha Araújo Firmo; Luís Cláudio Nascimento da Silva; Raimundo Nonato Diniz Costa Filho; Raimunda Nonata Fortes Carvalho Neta; Débora Batista Pinheiro Pinheiro Sousa (Environmental Monitoring and Assessment, 2024)

Bibliometric analysis of pumpkin seed proteins: A review of the multifunctional properties of their hydrolysates and future perspectives - Ana Flávia Coelho Pacheco; Flaviana Coelho Pacheco; Jeferson Silva Cunha; Fabio Ribeiro dos Santos; Jean Carlos Coelho Pacheco; Kely de Paula Correa; Wilson de Almeida Orlando Junior; Paulo Henrique Costa Paiva; Bruno Ricardo de Castro Leite Junior (Food Bioscience, 2024)

Epidemiological and clinical profile of HTLV-1 patients: a closer look at a reference center in Bahia, Brazil - Jéssica Oliveira de Souza Nascimento; Daniele Leite Alves; Ana Flávia Novaes; Qesya Rodrigues Ferreira; Felipe de Oliveira Andrade; Roberta Muniz Luz Silva; Saadia Oliveira Ribeiro; Riviane Santana Souza; Luciane Amorim Santos; Thessika Hialla Almeida Araújo; Guilherme Barreto Campos; Filipe Ferreira de Almeida Rego; et al. (VirusDisease, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Assessment of the presence of Acinetobacter spp. resistant to β-lactams in commercial ready-to-eat salad samples - Ana Costa-Ribeiro; Sarah Azinheiro; Sandra Mota; Marta Prado; Alexandre Lamas; Alejandro Garrido-Maestu (Food Microbiology, 2024)

Association of a Skin Dressing Made With the Organic Part of Marine Sponges and Photobiomodulation on the Wound Healing in an Animal Model - Abdias Fernando Simon Sales; Karolyne dos Santos Jorge Sousa; Amanda de Souza; Mirian Bonifacio; Tiago Akira Tashiro Araújo; Matheus de Almeida Cruz; Márcia Busanello Costa; Daniel Araki Ribeiro; Lívia Assis; Cintia Cristina Santi Martignago; Ana Cláudia Rennó (Marine Biotechnology, 2024)

Nitrogen fertilization increased grass litter decomposition in a tropical agroforestry system - Maria Karoline de Carvalho Rodrigue Sousa; Luciano Cavalcante Muniz; Valéria Xavier de Oliveira Apolinário; Joaquim Bezerra Costa; Ana María Herrera-Angulo; José Carlos Batista Dubeux; Victor Roberto Ribeiro Reis; Thaís Santos Figueiredo; Raabe Alves Souza; Erika Gonçalves Corrêa; Janerson José Coelho (Agroforestry Systems, 2024)

A novel molecule reduces cocoon production loss in BmNPV-infected Bombyx mori larvae - Jully Jesus De La Cruz Cisneros; Lucas Costa Cabral; Daniel Caligari; Alessandra Aparecida Silva; Alex Sandro Gularte Chiarello; Lucinéia de Fátima Chasko Ribeiro; Rose Meire Costa; Adriana Aparecida Sinópolis Gigliolli; Ana Silvia Lapenta; Anelise Cardoso Ramos; Flávio Augusto Vicente Seixas; Maria Aparecida Fernandez (International Journal of Tropical Insect Science, 2024)

Starvation-induced autophagy modulates spermatogenesis and sperm quality in Nile tilapia - Camila Ferreira Sales; Ana Paula Barbosa Pinheiro; Yves Moreira Ribeiro; Davidson Peruci Moreira; Ronald Kennedy Luz; Rafael Magno Costa Melo; Elizete Rizzo (Theriogenology, 2024)

How sustainable are recreational practices on Brazilian Amazon beaches? - Luci Cajueiro Carneiro Pereira; Rubem Manoel Coelho Pessoa; Rosigleyse Correa de Sousa-Felix; Ana Beatriz Brito Dias; Brenda Ribeiro Padilha da Silva; Rauquírio Marinho da Costa (Journal of Outdoor Recreation and Tourism, 2024)

UPLC-QTOF-MS/MS characterization of a fraction enriched in saponins from Sarcomphalus joazeiro species and evaluation of the antibacterial activity against multidrug-resistant bacteria - Ana Raquel Pereira da Silva; Maria do Socorro Costa; Nara Juliana Santos Araújo; Gabriel Gonçalves Alencar; Paulo Riceli Vasconcelos Ribeiro; Josean Fechine Tavares; Jacqueline Cosmo Andrade Pinheiro; Henrique Douglas Melo Coutinho (South African Journal of Botany, 2024)

UPLC–QTOF-MS/MS analysis of saponin-enriched fractions from Calliandra umbellifera Benth and evaluation of antibacterial activity against multidrug-resistant bacteria - Maria do Socorro Costa; Ana Raquel Pereira da Silva; Nara Juliana Santos Araújo; Cícera Laura Roque Paulo; Paulo Roberto Vieira Ribeiro; Josean Fechine Tavares; Jacqueline Cosmo Andrade Pinheiro; Henrique Douglas Melo Coutinho (Phytochemistry Letters, 2024)

Long-term effects of embryonic exposure to benzophenone-3 on neurotoxicity and behavior of adult zebrafish - Ana Luisa Pires Moreira; Juliana Alves Costa Ribeiro Souza; Jéssica Ferreira de Souza; João Paulo Medeiros Mamede; Davi Farias; Ana Carolina Luchiari (Science of The Total Environment, 2024)

The impact of fast-growing eucalypt plantations on C emissions in tropical soil: effect of belowground and aboveground C inputs - Rafael da Silva Teixeira; Daniela Cristina Costa; Valéria Santos Cavalcante; Ricardo Cardoso Fialho; Ana Paula Mendes Teixeira; Rodrigo Nogueira de Sousa; Aline de Almeida Vasconcelos; Ivo Ribeiro da Silva (Environmental Monitoring and Assessment, 2024)

Outdoor airborne allergens: Characterization, behavior and monitoring in Europe - Łukasz Grewling; Helena Ribeiro; Celia Antunes; Godfrey Philliam Apangu; Sevcan Çelenk; Ana Costa; Ibon Eguiluz-Gracia; Ana Galveias; Nestor Gonzalez Roldan; Mirela Lika; Donát Magyar; Moises Martinez-Bracero; et al. (Science of The Total Environment, 2023)

RETRACTED: Collapse of scallop Nodipecten nodosus production in the tropical Southeast Brazil as a possible consequence of global warming and water pollution - Cristiane Thompson; Leonardo Bacha; Pedro Henrique C. Paz; Marcelo de Assis Passos Oliveira; Braulio Cherene Vaz Oliveira; Claudia Omachi; Caroline Chueke; Marcela de Lima Hilário; Michele Lima; Luciana Leomil; Thais Felix-Cordeiro; Thalya Lou Cordeiro da Cruz; et al. (Science of The Total Environment, 2023)

Unintended consequences of valuing the contributions of non-native species: misguided conservation initiatives in a megadiverse region - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Carlos Bernardo Mascarenhas Alves; Marlene Sofia Arcifa; Valter M. Azevedo-Santos; Marcelo Fulgêncio Guedes Brito; Pâmella Silva de Brito; Paula Maria Gênova de Castro Campanha; Fernando Rogério Carvalho; Gabriel Costa da Costa; Mario Alberto Cozzuol; Almir Manoel Cunico; et al. (Biodiversity and Conservation, 2023)

Essential oil constituents as the chemosystematic markers in Eugenia L. (Myrtaceae): An evolutionary perspective - Raisa Maria Silveira; Fernando Heberson Menezes; Igor Gonçalves Lima; Ana F. F. Urano Carvalho; Mariana de Oliveira Bünger; Itayguara Ribeiro da Costa (South African Journal of Botany, 2023)

Effect from dinoponeratoxin M-PONTXDq3a arginine and lysine substituted analogues against Staphylococcus aureus strains - Pedro Nonato da Silva Júnior; João Victor Serra Nunes; Bruna Ribeiro Duque; Ana Júlia Batista Pereira; Emanuel Paula Magalhães; Cyntia Silva Oliveira; Katielle Albuquerque Freire; Cibele Nicolaski Pedron; Vani Xavier Oliveira; Tiago Lima Sampaio; Alice Maria Costa Martins (Toxicon, 2023)

Evaluation of Covalent Organic Frameworks for the low-cost, rapid detection of Shiga Toxin-producing Escherichia coli in ready-to-eat salads - Ana Costa-Ribeiro; Sarah Azinheiro; Soraia P.S. Fernandes; Alexandre Lamas; Marta Prado; Laura M. Salonen; Alejandro Garrido-Maestu (Analytica Chimica Acta, 2023)

Dietary tannin and different breeds alter the fatty acid profile and sensory properties of artisanal goat coalho cheese - Élice Brunelle Lessa dos Santos; Camila Fraga da Costa; Sheyla Priscila Oliveira do Nascimento; Ana Paula Ribeiro da Silva; Aline Silva de Sant’ana; Raquel Guidetti Vendruscolo; Francesca Silva Dias; Cedenir Pereira de Quadros; Roger Wagner; Daniel Ribeiro Menezes (Small Ruminant Research, 2023)

Stable Polyphenol Oxidase Produced by Pleurotus pulmonarius from Fermented Peach-Palm and Cocoa Wastes - Lucas Ribeiro de Carvalho; Débora Reis Santos; Camilla Silveira dos Santos Lima; Rosane Marina Peralta; Cristina Giatti Marques de Souza; Ana Paula Trovatti Uetanabaro; Erik Galvão Paranhos da Silva; Andréa Miura da Costa (BioEnergy Research, 2023)

Terpenic profile of the essential oil of Symphyopappus cuneatus (DC.) Sch.Bip. ex Baker and its effects on antibiotic resistance in vitro - José Bezerra de Araújo-Neto; Maria Milene Costa da Silva; Antonia Thassya Lucas dos Santos; Andressa Brandão de Souza; Cícera Datiane de Morais Oliveira-Tintino; Luiz Everson da Silva; Cleiton de Oliveira; Wanderlei do Amaral; Cícero Deschamps; João Tavares Calixto-Júnior; Jaime Ribeiro-Filho; Henrique Douglas Melo Coutinho; et al. (South African Journal of Botany, 2023)

Extruded urea levels in lamb supplementation in rainy tropical savanna conditions: the triad host-gastrointestinal nematodes-environment - Francisca Fernanda da Silva Roberto; Gelson dos Santos Difante; Roberto Germano Costa; Fernando de Almeida Borges; Luis Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Neila Lidiany Ribeiro; Jéssica Gomes Rodrigues; Marislayne de Gusmão Pereira; Gabriela Oliveira de Aquino Monteiro; Emmanuel Lievio de Lima Véras; Antonio Leandro Chaves Gurgel; et al. (Tropical Animal Health and Production, 2023)

Brazilian Semiarid Bradyrhizobium Strains Increase Nitrogen Accumulation and Modulate Physiological Parameters to Enable Superior Grain Production in Soybean Genotypes - Luis Borges Rocha; Elaine Martins da Costa; Ana Clara Martins de Sousa Ribeiro; Jasmine Ferreira dos Santos; Rafael de Souza Miranda; Amanda Soares Santos; Stelamaris de Oliveira Paula-Marinho; Bruno Sousa Figueiredo da Fonseca; Fatima Maria de Souza Moreira (Journal of Soil Science and Plant Nutrition, 2023)

Endothelial progenitor cell response to a multicomponent exercise training program in adults with cardiovascular risk factors - Suiane Cavalcante; Manuel Teixeira; Marisol Gouveia; Ana Duarte; Miriam Ferreira; Maria I. Simões; Maria Conceição; Mariana Costa; Ilda P. Ribeiro; Ana Cristina Gonçalves; José Oliveira; Fernando Ribeiro (German Journal of Exercise and Sport Research, 2023)

An innovative insecticidal approach based on plant protease inhibitor and Bt protoxins inhibits trypsin-like activity in zebrafish - Íris Flávia Sousa Gonçalves; Cleyton de Sousa Gomes; Luiz Carlos Pereira Almeida Filho; Juliana Alves da Costa Ribeiro Souza; Bruno Anderson Matias Rocha; Pedro Filho Noronha de Souza; Augusto Cézar Vasconcelos de Freitas Júnior; Ana Fontenele Urano Carvalho; Davi Farias (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Neuro-COVID-19 With or Without the Multisystem Inflammatory Syndrome (MIS-C): A Single-Center Study - Aline Almeida Bentes; Walter Rebuite dos Santos Junior; Natalia Lima Pessoa; Thais Alkifeles Costa; Gabriela Fernanda Garcia Oliveira; Lilian Martins Oliveira Diniz; Bruna Ribeiro Torres; Daniela Caldas Teixeira; Renata Barandas Mendes; Ana Beatriz Alvim Avelar; Marco Antônio Campos; Erna Geessien Kroon; et al. (Journal of Molecular Neuroscience, 2023)

Intramuscular compatibility of an injectable anti-inflammatory nanodispersion from a standardized Bixa orellana oil (Chronic®): a toxicological study in Wistar rats - Helison de Oliveira Carvalho; Ana Laura Ribeiro Sauma; Aline Lopes do Nascimento; Abrahão Victor Tavares de Lima Teixeira; Danna Emanuelle Santos Gonçalves; Lauana Gomes; Gabriel da Costa Furtado; Heitor Ribeiro da Silva; Gisele Custódio de Souza; Arlindo César Matias Pereira; José Carlos Tavares Carvalho (Inflammopharmacology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Effect of experimental toothpaste containing hydroxyapatite nanoparticles and propolis, with and without fluoride, on the microcosm biofilm and enamel demineralization - Caroline Fernanda da Silva Ribeiro; Aline Dionizio; Tamara Teodoro Araújo; Chelsea Maria Vilas Boas Feitosa Rodrigues; Amanda Costa Mattos; Letícia Galli Otaviano; Larissa Tercília Grizzo; Ana Carolina Magalhães; Marília Afonso Rabelo Buzalaf (Biofouling, 2023)

Malassezia spp. and Candida spp. from patients with psoriasis exhibit reduced susceptibility to antifungals - Rossana de Aguiar Cordeiro; Ane Teles Reis; Xinaida Taligare Vasconcelos Lima; Ana Raquel Colares de Andrade; Ana Luiza Ribeiro Aguiar; Fernando Victor Monteiro Portela; Lívia Maria Galdino Pereira; Santiago Gonçalves Bezerra Moura; Bruno Nascimento da Silva; Reginaldo Gonçalves de Lima-Neto; Débora Castelo-Branco Souza Collare Maia; Marcos Fábio Gadelha Rocha; et al. (Brazilian Journal of Microbiology, 2023)

Antitumor lectins from algae: A systematic review - Maria Carla Santana de Arruda; Maria Rafaele Oliveira Bezerra da Silva; Vivianne Lays Ribeiro Cavalcanti; Romero Marcos Pedrosa Costa Brandao; Daniela de Araújo Viana Marques; Luiza Rayanna Amorim de Lima; Ana Lúcia Figueiredo Porto; Raquel Pedrosa Bezerra (Algal Research, 2023)

Hot Vents Beneath an Icy Ocean: The Aurora Vent Field, Gakkel Ridge, Revealed - Eva Ramirez-Llodra; Claudio Argentino; Maria Baker; Antje Boetius; Carolina Costa; Håkon Dahle; Emily Denny; Pierre-Antoine Dessandier; Mari Eilertsen; Benedicte Ferre; Christopher German; Kevin Hand; et al. (Oceanography, 2023)
Evidence of hydrothermal venting on the ultra-slow spreading Gakkel Ridge in the Central Arctic Ocean has been available since 2001, with first visual evidence of black smokers on the Aurora Vent Field obtained in 2014. But it was not until 2021 that the first ever remotely operated vehicle (ROV) dives to hydrothermal vents under permanent ice cover in the Arctic were conducted, enabling the collection of vent fluids, rocks, microbes, and fauna. In this paper, we present the methods employed for deep-sea ROV operations under drifting ice. We also provide the first description of the Aurora Vent Field, which includes three actively venting black smokers and diffuse flow on the Aurora mound at ~3,888 m depth on the southern part of the Gakkel Ridge (82.5°N). The biological communities are dominated by a new species of cocculinid limpet, two small gastropods, and a melitid amphipod. The ongoing analyses of Aurora Vent Field samples will contribute to positioning the Gakkel Ridge hydrothermal vents in the global biogeographic puzzle of hydrothermal vents.

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Promethazine inhibits efflux, enhances antifungal susceptibility and disrupts biofilm structure and functioning in Trichosporon - Ana Luiza Ribeiro Aguiar; Bruno Nascimento da Silva; Nicole de Mello Fiallos; Lívia Maria Galdino Pereira; Maria Laína Silva; Pedro Freitas Santos Manzi de Souza; Fernando Victor Monteiro Portela; José Júlio Costa Sidrim; Marcos Fábio Gadelha Rocha; Débora Souza Collares Maia Castelo-Branco; Rossana de Aguiar Cordeiro (Biofouling, 2023)

In vitro effect of the iron chelator deferiprone on the antimicrobial susceptibility and biofilms of Burkholderia pseudomallei - Glaucia Morgana de Melo Guedes; Késia Veras Costa Ribeiro; Emanuela Silva de Araújo; Vinícius Carvalho Pereira; Ana Carla de Castro Freitas Soares; Alyne Soares Freitas; Rossana de Aguiar Cordeiro; José Júlio Costa Sidrim; Marcos Fábio Gadelha Rocha; Débora de Souza Collares Maia Castelo-Branco (Biofouling, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Environmental assessment of Neotropical streams using fish as bioindicators: a multibiomarker and integrated approach - Nédia de Castilhos Ghisi; Crislei Larentis; Elton Celton de Oliveira; Mayara Pereira Neves; Arielli Giachini Zavaski; Aliciane de Almeida Roque; Catia Cappelli Wachtel; Ana Paula da Silva; Emanuele Barreto Stange de Lima; Giovanni de Oliveira Nagasawa Costa; Joao Paulo de Arruda Amorim; Ciro Alberto de Oliveira Ribeiro; et al. (Hydrobiologia, 2022)

Heterologous extracellular DNA facilitates the development of Trichosporon asahii and T. inkin biofilms and enhances their tolerance to antifungals - Lívia Maria Galdino Pereira; Ana Raquel Colares de Andrade; Fernando Victor Monteiro Portela; Ana Luiza Ribeiro Aguiar; Bruno Nascimento da Silva; Santiago Gonçalves Bezerra Moura; Mariana Lara Mendes Pergentino; Marcos Fábio Gadelha Rocha; José Júlio da Costa Sidrim; Débora de Souza Collares Maia Castelo Branco; Rossana de Aguiar Cordeiro (Biofouling, 2022)

Antimicrobial resistance and genetic background of non-typhoidal Salmonella enterica strains isolated from human infections in São Paulo, Brazil (2000–2019) - Aline Parolin Calarga; Marco Tulio Pardini Gontijo; Luiz Gonzaga Paula de Almeida; Ana Tereza Ribeiro de Vasconcelos; Leandro Costa Nascimento; Taíse Marongio Cotrim de Moraes Barbosa; Thalita Mara de Carvalho Perri; Silvia Regina dos Santos; Monique Ribeiro Tiba-Casas; Eneida Gonçalves Lemes Marques; Cleide Marques Ferreira; Marcelo Brocchi (Brazilian Journal of Microbiology, 2022)

Discovery and genome sequencing of a new virus related to members of the family Tymoviridae, isolated from mosquitoes of the genus Mansonia in Brazil - Keissy Karoline Pinheiro Miranda; Glennda Juscely Pereira Galvão; Pedro Arthur da Silva Araújo; Ana Claudia da Silva Ribeiro; Sandro Patroca da Silva; Poliana da Silva Lemos; Lívia Carício Martins; Márcio Roberto Teixeira Nunes; Pedro Fernando da Costa Vasconcelos; Vânia da Costa Ferreira; Fábio Medeiros da Costa; Rosemary Aparecida Roque; et al. (Archives of Virology, 2022)
A new virus, named Mutum virus, related to members of the family Tymoviridae , was isolated from mosquitoes ( Mansonia spp.) in clone C6/36 cells, and its complete genome was sequenced. Its genome is 6494 nt in size with an organization resembling that of tymovirids. The isolated virus is phylogenetically related to two viruses isolated from Culex spp. mosquitoes: Ek Balam virus, reported in Mexico, and Culex-originated Tymoviridae-like virus, isolated in China. The results of this study suggest that this virus is a new member of the family Tymoviridae.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Hydrochlorothiazide use is associated with the risk of cutaneous and lip squamous cell carcinoma: A systematic review and meta-analysis - Ana Cláudia de Macedo Andrade; Fernanda Aragão Felix; Glória Maria França; Isabella Lima Arrais Ribeiro; Carlos Augusto Galvão Barboza; Ricardo Dias de Castro; Antônio de Lisboa Lopes Costa (European Journal of Clinical Pharmacology, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Enterococcus faecalis and Candida albicans dual-species biofilm: establishment of an in vitro protocol and characterization - Nicole de Mello Fiallos; Ana Luiza Ribeiro Aguiar; Bruno Nascimento da Silva; Marcos Fábio Gadelha Rocha; José Júlio Costa Sidrim; Débora Castelo Branco de Souza Collares Maia; Rossana de Aguiar Cordeiro (Biofouling, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Artificial Intelligence as a Combinatorial Optimization Strategy for Cellulase Production by Trichoderma stromaticum AM7 Using Peach-Palm Waste Under Solid-State Fermentation - Camila Oliveira Bezerra; Lucas Lima Carneiro; Elck Alemeida Carvalho; Thiago Pereira das Chagas; Lucas Ribeiro de Carvalho; Ana Paula Trovatti Uetanabaro; Gervásio Paulo da Silva; Erik Galvão Paranhos da Silva; Andréa Miura da Costa (BioEnergy Research, 2021)

Pollen morphology of Senegalia Raf. species and related genera (Leguminosae: Caesalpinioideae: mimosoid clade) - Ana Flávia Trabuco Duarte; Pétala Gomes Ribeiro; André Luiz da Costa Moreira; Luciano Paganucci de Queiroz; Francisco de Assis Ribeiro dos Santos (Palynology, 2021)

Productive and reproductive performance of females F1 Holstein x Gir daughters of proven bulls - Maria Dulcinéia da Costa; Alvimara Felix dos Reis; José Reinaldo Mendes Ruas; Gislane Evangelista Bispo; Vicente Ribeiro Rocha Júnior; Virgílio Mesquita Gomes; Tânia Lino Fiúza; Mary Ana Petersen Rodriguez; Mário Henrique França Mourthé; Daniel Ananias de Assis Pires (Tropical Animal Health and Production, 2021)

Seasonality Effects on Antibacterial and Antibiotic Potentiating Activity against Multidrug-Resistant Strains of Escherichia coli and Staphylococcus aureus and ATR-FTIR Spectra of Essential Oils from Vitex gardneriana Leaves - Raimundo Luiz Silva Pereira; Thiago Sampaio de Freitas; Priscilla Ramos Freitas; Ana Carolina Justino de Araújo; Fábia Ferreira Campina; Kleber Ribeiro Fidelis; Jean Parcelli Costa do Vale; Antônio César Honorato Barreto; Henrique Douglas Melo Coutinho; Paulo Nogueira Bandeira; Alexandre Magno Rodrigues Teixeira; Hélcio Silva dos Santos (Current Microbiology, 2020)

Forest cover influences zooplanktonic communities in Amazonian streams - Ana Caroline Alcântara Missias Gomes; Leonardo Fernandes Gomes; Iris Roitman; Hasley Rodrigo Pereira; Antonio Felipe Couto Junior; Elizabeth Maria Mamede da Costa; Mariana Lessa Carneiro da Silva; Tamiel Khan Baiocchi Jacobson; Rômulo José da Costa Ribeiro; Reinaldo José de Miranda Filho; Mario Lucio de Avila; Ludgero Cardoso Galli Vieira (Aquatic Ecology, 2020)

Effect of different roughage sources associated banana pseudostem hay on the nutritional and behavioral parameters and performance of F1 Holstein/Zebu lactation cows - Walber de Oliveira Rabelo; Vicente Ribeiro Rocha Júnior; Flávio Pinto Monção; Natanael Mendes Costa; João Paulo Sampaio Rigueira; Bruno Pereira de Souza; Ana Marla Oliveira Durães; Dorismar David Alves; Felipe Shindy Aiura; Cinara da Cunha Siqueira Carvalho; Daniel Ananias de Assis Pires (Tropical Animal Health and Production, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Fifteen years of a nationwide culture collection of Neisseria gonorrhoeae antimicrobial resistance in Portugal - Miguel Pinto; João Carlos Rodrigues; Rui Matias; Ivone Água-Doce; Dora Cordeiro; Cristina Correia; João Paulo Gomes; Maria José Borrego; Filipa Alegria; Ana Jacinta Piedade; Maria Beatriz Tomaz; Cristina Toscano; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Nutrient intake and ingestive behavior of feedlot steers fed with licuri cake - Marceliana da Conceição Santos; Robério Rodrigues Silva; Fabiano Ferreira da Silva; Aroldo Brandão de Oliveira; Laize Vieira Santos; Tarcísio Ribeiro Paixão; Ana Paula Gomes da Silva; João Wilian Dias Silva; Rodrigo Paiva Barbosa; Gabriel Dallapicola da Costa (Tropical Animal Health and Production, 2020)

Are Cowpea-Nodulating Bradyrhizobial Communities Influenced by Biochar Amendments in Soils? Genetic Diversity and Symbiotic Effectiveness Assessment of Two Agricultural Soils of Brazilian Drylands - Gilmar Silva Oliveira; Pâmella Thalita Souza Sena; Tailane Ribeiro do Nascimento; Reginaldo Alves Ferreira Neto; Juliana Ribeiro Costa Pereira; Lindete Míria Vieira Martins; Ana Dolores Santiago de Freitas; Diana Signor; Paulo Ivan Fernandes-Júnior (Journal of Soil Science and Plant Nutrition, 2020)

Evaluation of the potential of coal fly ash produced by gasification as hexavalent chromium adsorbent - Priscila Baruffi Ribeiro; Vitoria Olave de Freitas; Karine Machry; Ana Rosa Costa Muniz; Gabriela Silveira da Rosa (Environmental Science and Pollution Research, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Yellow fever virus modulates cytokine mRNA expression and induces activation of caspase 3/7 in the human hepatocarcinoma cell line HepG2 - Gustavo Moraes Holanda; Samir Mansour Morais Casseb; Juarez Antônio Simões Quaresma; Pedro Fernando Costa Vasconcelos; Ana Cecília Ribeiro Cruz (Archives of Virology, 2019)

Adequacy of Drosophila melanogaster as prey for the development and reproduction of Coleomegilla maculata - Halina Schultz; Eduardo da Silva; Elen de Lima Aguiar-Menezes; André Luis Santos Resende; Janaina Ribeiro Costa Rouws; Ana Rafaela Moreira da Silva (BioControl, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Exploring anammox bacteria ecology to improve nitrogen removal in wastewater treatment - Hugo Ribeiro; I Made Wijaya; Verónica Soares-Santos; Alexandra Santos; Paula Salgado; Ana Machado; Sérgia Costa-Dias; Adriano Bordalo; Catarina Teixeira (Frontiers in Marine Science, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Screening of plant growth promotion ability among bacteria isolated from field-grown sorghum under different managements in Brazilian drylands - Jéssica Fernanda da Silva; Thaise Rosa da Silva; Indra Elena Costa Escobar; Ana Carla Resende Fraiz; Jonnathan Whiny Moraes dos Santos; Tailane Ribeiro do Nascimento; João Marcos Rodrigues dos Santos; Samuel James Windsor Peters; Roseli Freire de Melo; Diana Signor; Paulo Ivan Fernandes-Júnior (World Journal of Microbiology and Biotechnology, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

gsimcli: a geostatistical procedure for the homogenisation of climatic time series - Sara Ribeiro; Júlio Caineta; Ana Cristina Costa; Roberto Henriques (International Journal of Climatology, 2017)
Climate data homogenisation is of major importance in monitoring climate change and in validating weather forecasts, general circulation and regional atmospheric models, modelling of erosion and drought monitoring, among other impact studies. Discontinuities in the time series, also named inhomogeneities, may lead to biased conclusions in such studies, so they should be detected and corrected. Previous studies have suggested a geostatistical stochastic approach, which uses Direct Sequential Simulation ( DSS ), as a promising methodology for the homogenisation of precipitation data series. Based on the spatial and temporal correlation between the neighbouring stations, DSS calculates local probability density functions at a candidate station to detect inhomogeneities. Here, we present a new method named gsimcli (Geostatistical SIMulation for the homogenisation of CLImate data), which is an improved and extended version of that approach. This technique is novel in its incorporation of spatial correlation metrics for the homogenisation of climate time series. The method's performance is assessed with annual and monthly precipitation, and monthly temperature data from two regions of the COST‐HOME benchmark data set, and the results are compared using performance metrics. We also evaluate a semi‐automatic version of the gsimcli method, which performs additional adjustments for sudden shifts. Both gsimcli versions provided similar results in the homogenisation of annual series. The gsimcli method was more efficient in the homogenisation of the benchmark's precipitation series than the original geostatistical approach. The gsimcli approach performed more closely to state‐of‐the‐art procedures in the homogenisation of monthly data than in the homogenisation of annual data. We expect that the proposed procedure will open new perspectives for the development of techniques that detect and correct inhomogeneities in climate data with monthly and sub‐monthly resolution.

An integrated approach to understand the mechanisms underlying salt stress tolerance in Casuarina glauca and its relation with nitrogen-fixing Frankia Thr - Ana I. Ribeiro-Barros; Mário da Costa; Nuno Duro; Inês Graça; Paula Batista-Santos; Tiago F. Jorge; Fernando C. Lidon; K. Pawlowski; Carla António; José C. Ramalho (Symbiosis, 2016)

Chloramphenicol residues found in milk processed in Northern Parana, Brazil - Joice Sifuentes dos Santos; Bruno Garcia Botaro; Ana Beatriz da Costa Ribeiro; Samera Rafaela Bruzaroski; Italo Trento; Elsa Helena Walter Santana (Journal of Consumer Protection and Food Safety, 2016)

The impact of salinity on the symbiosis between Casuarina glauca Sieb. ex Spreng. and N2-fixing Frankia bacteria based on the analysis of Nitrogen and Carbon metabolism - Nuno Duro; Paula Batista-Santos; Mário da Costa; Rodrigo Maia; Isabel V. Castro; Margarida Ramos; José C. Ramalho; Katharina Pawlowski; Cristina Máguas; Ana Ribeiro-Barros (Plant and Soil, 2016)

Long‐term elevated air [ CO 2 ] strengthens photosynthetic functioning and mitigates the impact of supra‐optimal temperatures in tropical Coffea arabica and C. canephora species - Weverton P. Rodrigues; Madlles Q. Martins; Ana S. Fortunato; Ana P. Rodrigues; José N. Semedo; Maria C. Simões‐Costa; Isabel P. Pais; António E. Leitão; Filipe Colwell; Luis Goulao; Cristina Máguas; Rodrigo Maia; et al. (Global Change Biology, 2016)
The tropical coffee crop has been predicted to be threatened by future climate changes and global warming. However, the real biological effects of such changes remain unknown. Therefore, this work aims to link the physiological and biochemical responses of photosynthesis to elevated air [ CO 2 ] and temperature in cultivated genotypes of C offea arabica L. (cv. Icatu and IPR 108) and Coffea canephora cv. Conilon CL 153. Plants were grown for ca. 10 months at 25/20 °C (day/night) and 380 or 700 μl CO 2 l −1 and then subjected to temperature increase (0.5 °C day −1 ) to 42/34 °C. Leaf impacts related to stomatal traits, gas exchanges, C isotope composition, fluorescence parameters, thylakoid electron transport and enzyme activities were assessed at 25/20, 31/25, 37/30 and 42/34 °C. The results showed that (1) both species were remarkably heat tolerant up to 37/30 °C, but at 42/34 °C a threshold for irreversible nonstomatal deleterious effects was reached. Impairments were greater in C. arabica (especially in Icatu) and under normal [ CO 2 ]. Photosystems and thylakoid electron transport were shown to be quite heat tolerant, contrasting to the enzymes related to energy metabolism, including RuBis CO , which were the most sensitive components. (2) Significant stomatal trait modifications were promoted almost exclusively by temperature and were species dependent. Elevated [ CO 2 ], (3) strongly mitigated the impact of temperature on both species, particularly at 42/34 °C, modifying the response to supra‐optimal temperatures, (4) promoted higher water‐use efficiency under moderately higher temperature (31/25 °C) and (5) did not provoke photosynthetic downregulation. Instead, enhancements in [ CO 2 ] strengthened photosynthetic photochemical efficiency, energy use and biochemical functioning at all temperatures. Our novel findings demonstrate a relevant heat resilience of coffee species and that elevated [ CO 2 ] remarkably mitigated the impact of heat on coffee physiology, therefore playing a key role in this crop sustainability under future climate change scenarios.

Validation of candidate reference genes for qRT-PCR studies in symbiotic and non-symbiotic Casuarina glauca Sieb. ex Spreng. under salinity conditions - Mário da Costa; Nuno Duro; P. Batista-Santos; José C. Ramalho; Ana I. Ribeiro-Barros (Symbiosis, 2015)

Unraveling the interactive effects of climate change and oil contamination on laboratory‐simulated estuarine benthic communities - Francisco J. R. C. Coelho; Daniel F. R. Cleary; Rui J. M. Rocha; Ricardo Calado; José M. Castanheira; Sílvia M. Rocha; Artur M. S. Silva; Mário M. Q. Simões; Vanessa Oliveira; Ana I. Lillebø; Adelaide Almeida; Ângela Cunha; et al. (Global Change Biology, 2015)
There is growing concern that modifications to the global environment such as ocean acidification and increased ultraviolet radiation may interact with anthropogenic pollutants to adversely affect the future marine environment. Despite this, little is known about the nature of the potential risks posed by such interactions. Here, we performed a multifactorial microcosm experiment to assess the impact of ocean acidification, ultraviolet B (UV‐B) radiation and oil hydrocarbon contamination on sediment chemistry, the microbial community (composition and function) and biochemical marker response of selected indicator species. We found that increased ocean acidification and oil contamination in the absence of UV‐B will significantly alter bacterial composition by, among other things, greatly reducing the relative abundance of Desulfobacterales , known to be important oil hydrocarbon degraders. Along with changes in bacterial composition, we identified concomitant shifts in the composition of oil hydrocarbons in the sediment and an increase in oxidative stress effects on our indicator species. Interestingly, our study identifies UV‐B as a critical component in the interaction between these factors, as its presence alleviates harmful effects caused by the combination of reduced pH and oil pollution. The model system used here shows that the interactive effect of reduced pH and oil contamination can adversely affect the structure and functioning of sediment benthic communities, with the potential to exacerbate the toxicity of oil hydrocarbons in marine ecosystems.

Germline CDKN2A mutations in Brazilian patients of hereditary cutaneous melanoma - Alexandre Leon Ribeiro de Ávila; Ana Cristina Victorino Krepischi; Luciana Facure Moredo; Talita Ferreira Marques Aguiar; Felipe Carneiro da Silva; Bianca Costa Soares de Sá; Amanda França de Nóbrega; Maria Isabel Waddington Achatz; João Pedreira Duprat; Gilles Landman; Dirce Maria Carraro (Familial Cancer, 2014)

Subversion of early innate antiviral responses during antibody-dependent enhancement of Dengue virus infection induces severe disease in immunocompetent mice - Vivian V. Costa; Caio T. Fagundes; Deborah F. Valadão; Thiago V. Ávila; Daniel Cisalpino; Rebeca F. Rocha; Lucas S. Ribeiro; Fernando R. Ascenção; Lucas M. Kangussu; Celso M. Q. Junior; Ruiz G. Astigarraga; Frederico L. Gouveia; et al. (Medical Microbiology and Immunology, 2014)

Development and validation of an experimental life support system for assessing the effects of global climate change and environmental contamination on estuarine and coastal marine benthic communities - Francisco J. R. C. Coelho; Rui J. M. Rocha; Ana C. C. Pires; Bruno Ladeiro; José M. Castanheira; Rodrigo Costa; Adelaide Almeida; Ângela Cunha; Ana Isabel Lillebø; Rui Ribeiro; Ruth Pereira; Isabel Lopes; et al. (Global Change Biology, 2013)
An experimental life support system ( ELSS ) was constructed to study the interactive effects of multiple stressors on coastal and estuarine benthic communities, specifically perturbations driven by global climate change and anthropogenic environmental contamination. The ELSS allows researchers to control salinity, pH , temperature, ultraviolet radiation ( UVR ), tidal rhythms and exposure to selected contaminants. Unlike most microcosms previously described, our system enables true independent replication (including randomization). In addition to this, it can be assembled using commercially available materials and equipment, thereby facilitating the replication of identical experimental setups in different geographical locations. Here, we validate the reproducibility and environmental quality of the system by comparing chemical and biological parameters recorded in our ELSS with those prevalent in the natural environment. Water, sediment microbial community and ragworm (the polychaete Hediste diversicolor ) samples were obtained from four microcosms after 57 days of operation. In general, average concentrations of dissolved inorganic nutrients ( NO 3 − ; NH 4 + and PO 4 −3 ) in the water column of the ELSS experimental control units were within the range of concentrations recorded in the natural environment. While some shifts in bacterial community composition were observed between in situ and ELSS sediment samples, the relative abundance of most metabolically active bacterial taxa appeared to be stable. In addition, ELSS operation did not significantly affect survival, oxidative stress and neurological biomarkers of the model organism Hediste diversicolor . The validation data indicate that this system can be used to assess independent or interactive effects of climate change and environmental contamination on benthic communities. Researchers will be able to simulate the effects of these stressors on processes driven by microbial communities, sediment and seawater chemistry and to evaluate potential consequences to sediment toxicity using model organisms such as Hediste diversicolor .

Prevalence of the bla SHV Gene in Klebsiella pneumoniae Isolates Obtained from Hospital and Community Infections and from the Microbiota of Healthy Individuals in Recife, Brazil - Dyana Leal Veras; Luiz Carlos Alves; Fábio André Brayner; Duschinka Ribeiro Duarte Guedes; Maria Amélia Vieira Maciel; Cíntia Renata Costa Rocha; Ana Catarina de Souza Lopes (Current Microbiology, 2011)

Variation in grafted European chestnut and hybrids by microsatellites reveals two main origins in the Iberian Peninsula - Santiago Pereira-Lorenzo; Rita Maria Lourenço Costa; Ana María Ramos-Cabrer; Carla Alexandra Marques Ribeiro; Marta Filipa Serra da Silva; George Manzano; Teresa Barreneche (Tree Genetics & Genomes, 2010)

Detailed analysis of expression and promoter methylation status of apoptosis-related genes in prostate cancer - João R. Carvalho; Luísa Filipe; Vera L. Costa; Franclim Ricardo Ribeiro; Ana T. Martins; Manuel R. Teixeira; Carmen Jerónimo; Rui Henrique (Apoptosis, 2010)

Effect of COX-2 inhibitor after TNBS-induced colitis in wistar rats - Ana Paula Ribeiro Paiotti; Sender Jankiel Miszputen; Celina Tizuko Fujiyama Oshima; Henrique de Oliveira Costa; Daniel Araki Ribeiro; Marcello Franco (Journal of Molecular Histology, 2009)